Upregulation of TSHR, TTF-1, and PAX8 in Nodular Goiter Is Associated with Iodine Deficiency in the Follicular Lumen - Huibin Huang; Lijun Chen; Bo Liang; Huiyao Cai; Qingyan Cai; Yaxiong Shi (International Journal of Endocrinology)
Objective. It has been testified that iodine regulates thyroid function by controlling thyroid-restricted genes expression and is closely related to diffuse goiter and thyroid dysfunction. However, the effects of follicular lumen iodine, the main form of iodine reserve in the body, on thyroid-restricted genes in nodular goiter are poorly understood. In this study, correlations between follicular lumen iodine and the expressions of thyroid stimulating hormone receptor (TSHR), its transcription factors TTF-1, and PAX8 in nodular goiter were investigated. Patients. In this study, 30 resection specimens clinically histopathologically confirmed to have nodular goiter and 30 normal thyroid specimens from adjacent tissues of nodular goiter are used. Measurement. Western blot immunohistochemistry was performed to assay TSHR, TTF-1, and PAX8 in thyrocytes of nodular goiter as well as in extranodular normal thyroid tissues. Meanwhile, follicular lumen iodine of both nodular goiter and extranodular normal thyroid tissues was detected as well. Results. The TSHR, TTF-1, and PAX8 in nodular goiter were significantly higher than those in the controls. The iodine content in nodular goiter was significantly lower than those in control tissues. Conclusion. Upregulation of TSHR, TTF-1, and PAX8 is associated with low follicular lumen iodine content in nodular goiter.